Building web applications with Visual Studio 2017 : using .NET Core and modern JavaScript frameworks - Japikse, Philip; Grossnicklaus, Kevin; Dewey, Ben (Apress, 2017)
"Learn how to build web applications from three Microsoft MVPs. You will be able to compare and contrast several frameworks and select the best one for your needs. With the release of .NET Core and Visual Studio 2017, you can deploy applications to multiple operating systems. And with the rising popularity of JavaScript UI frameworks, you can choose whether to stay with ASP.NET Core MVC or use a JavaScript framework. Building Web Applications with Visual Studio 2017 shows you how to build a site in Core MVC, and the three most popular JavaScript frameworks: Angular 2, React, and Aurelia. What You Will Learn: * Build a data access layer with Entity Framework Core * Build a RESTful service with ASP.NET Core MVC * Build a website with ASP.NET Core MVC and Bootstrap * Build the same website in Angular 2, React, and Aurelia. Who This Book Is For: Intermediate to advanced .NET developers."--Resumé vydavatele
Obsahuje rejstřík
Keywords: Microsoft Visual Studio (software); WWW aplikace; Microsoft .NET Framework (software); Microsoft Visual Studio; web applications; Microsoft .NET Framework; příručky; handbooks and manuals